Efficacy of dexamethasone implant in the management of chronic central serous chorioretinopathy without choroidal neovascularization - Umesh Chandra Behera; Anand S Brar; Anup Kelgaonkar; Jyotiranjan Sahoo; Raja Narayanan; SriniVas R Sadda (Indian Journal of Ophthalmology)
Purpose: To demonstrate the treatment efficacy of intravitreal dexamethasone (DEX) implant in chronic recurrent/persistent central serous chorioretinopathy (CSC). Design: Prospective, non-randomized, open-label study. Methods: In this study, subjects with chronic CSC without signs of choroidal neovascularization (CNV) received intravitreal DEX implant therapy. The primary outcome measure was the change in visual acuity. Changes in central macular thickness (CMT) and change in subfoveal choroidal thickness (SFCT) on optical coherence tomography (OCT), incidence of recurrent fluid, and safety of DEX implant were secondary outcome measures. Subjects were followed up for a minimum of 3 months after DEX implantation. Results: In total, 20 eyes of 20 subjects (mean age: 47 ± 9 years) with a median disease duration of 23.5 months were enrolled. With a single injection of DEX implant, a reduction in CMT was noted in 90% of eyes. Complete resolution of subretinal and intraretinal fluid was noted in 55% of eyes within 3 months of injection. A significant improvement in vision (mean Log MAR visual acuity: 0.66 ± 0.49 vs. 0.54 ± 0.45; P = 0.020), mean CMT (338 ± 110 microns to 238 ± 73 microns; P < 0.001) and SFCT (514 ± 95 microns to 445 ± 111 microns; P < 0.001) was noted over 3 months. Recurrent fluid was noted in 50% of eyes after a mean follow-up duration of 7 ± 4 months. Elevated intraocular pressure, managed by topical therapy, was noted in six eyes. Conclusion: The consistent improvement in visual acuity, fluid resolution, and reduction in choroidal thickness suggests a possible role for DEX implants in managing chronic CSC. A larger randomized trial is warranted.